Pengaruh Teknologi Terhadap Pengalaman Membaca Sastra: Studi Kasus Pada Pembaca E-book dan Buku Cetak dalam Membaca Novel Klasik Inggris - Hidayati, Eka (BASIS (Bahasa dan Sastra Inggris), 2024)
This study aims to investigate how technology influences the reading experience of English classic novels, specifically by comparing e-book and print book readers. Through online surveys and controlled experiments involving distinct participant groups, both quantitative and qualitative data were analyzed. The research aims to provide insights into differences in reading experiences based on the literary format. Surveys gather quantitative data on participants’ reading habits, preferences, and perceptions of e-books and print books. In contrast, the controlled experiments focus on qualitative aspects, observing participant engagement, comprehension, and emotional responses while reading classic novels in either format. By examining participant responses and behaviors, the study elucidates how technological advancements affect readers’ engagement with literary texts traditionally consumed in print. The primary objective is to offer new perspectives on the influence of technological mediums on our interaction with literary works. The research aim to shed light on the evolving landscape of reading practices in the digital age, providing valuable insights pertinent to educators, publishers, and readers seeking to understand the implications of technology on literature consumption and appreciation.